Work Values in the Generational Aspect on the Example of Younger Millennials of Saint Petersburg - Elizaveta Sergeevna Balatsiuk; Elizaveta Vitalevna Kresnikova (Интеракция. Интервью. Интерпретация)
The article examines the career trajectories and work values of thirty representatives of the generation of younger millennials living in St. Petersburg and employed in education and science, IT, industry and services, with a stable average income. Based on the analysis of semi-structured interviews, narratives about the importance of permanent employment of young people are described: the desired salary level, personal responsibility in the workplace, building relationships with colleagues, developing soft-skills and hard-skills, achieving stability and sustainability in life. Classism in the process of reproduction of labor values also remains a significant category. It is reflected in the narratives of informants about employment and is associated with gaining agency and independence in the process of gaining work experience.